Incidence and growth of uterine myoma after ovulation induction on 1100 infertile women in shahid Akbarabadi Hospital and Royan Institute - M Ashrafi; M Sadeghi; Z Montazeri; Sh Tavajjohi (JRI, 2000)
The aim of this study was to determine the incidence and growth rate of uterine myomas in users of ovulation induction drugs. Eleven hundred in fertile women who had undagone at least 5 cycles of ovulation induction, refering to Royan Institute and Akbarabadi Hospital were selected on the basis of easy access selection method. To study presence or absence of uterine myoma, all the patients were subjected to sonograply before ovulation induction The sonography was repeated after at least 5 cycles of ovulation induction and was compared with the initial sonography. Of the 1100 patients, 54 had myoma and of the 1046 myoma–free patients, 71 (6.8%) developed myoma later and of the 54 with initial myoma, 40 (%74) showed increased growth of their myoma. This study is a beginning for studies on the effect of ovulation induction on the growth rate of uterine myomas and may be a comparison basis for the incidenee and growth rate of myomas in an age matched control group of women.
Keywords: Uterine myoma, Infertility, Ovulation induction, Assisted Reproductive Techniques